Successful Intelligence and its Relationship to the Cognitive Holding Power among Umm Al-Qura University Female Students - Azouz, Asmaa Mohammad Hashem; Al-Harbi, Nawar Mohammad Saad (Journal of Educational and Psychological Sciences, 2024)
The study aims to identify the level of successful intelligence and the order of the cognitive holding power among Umm Al-Qura University female students, to define the relationship between them, to reveal the differences in both successful intelligence and cognitive holding power depending on the academic discipline and the academic grade variables, and the predictability of the cognitive holding power through successful intelligence among female university students, To achieve the objectives of the study, Al-Harbi Successful Intelligence Scale (2021) and Stevenson and Evans Cognitive Holding Power Scale (1994) were applied to a sample of 519 female undergraduate students who were selected using the stratified random method, The descriptive approach was used, The findings indicated that the female university students had a high level of successful intelligence and all its dimensions. They also had a high level of cognitive holding power and both its orders, The prevailing order among the study sample was the second order, The findings also showed an average direct relationship between cognitive holding power and successful intelligence, They also found statistically significant differences in successful intelligence and cognitive holding power attributable to the academic discipline variable in favor of female students in theoretical majors, and no differences attributable to the academic grade variable in successful intelligence and cognitive holding power, They also indicated the predictability of cognitive holding power through successful intelligence among female students, In view of the findings, the study recommends preparing courses and educational programs in order to improve and develop the learning environment, and paying attention to integrating successful intelligence skills with cognitive skills that represent the orders of cognitive holding power in the educational process among female university students.
Keywords: successful intelligence; cognitive holding power; Umm Al-Qura University female students